Impact of applying the theory of human becoming and self-care deficit theory of nursing on insomnia in after stroke urinary incontinence patients - Heltty Heltty; Sitorus Ratna; Haryanto Haryanto (Sciendo, 2024)
To determine the impact of applying the theory of human becoming and self-care deficit theory of nursing in overcoming insomnia in patients of urinary incontinence (UI) after stroke. Insomnia is a sleep disorder experienced by UI patients after stroke which can exacerbate problems related to brain damage and can complicate the recovery process.